2014
DOI: 10.1128/jvi.01876-14
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gammaherpesvirus 68 Reactivation from B Cells Requires IRF4 but Not XBP-1

Abstract: Gammaherpesviruses display tropism for B cells and, like all known herpesviruses, exhibit distinct lytic and latent life cycles. One well-established observation among members of the gammaherpesvirus family is the link between viral reactivation from latently infected B cells and plasma cell differentiation. Importantly, a number of studies have identified a potential role for a CREB/ATF family member, X-box binding protein 1 (XBP-1), in trans-activating the immediate early BZLF-1 or BRLF1/gene 50 promoters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…While the external cellular environment is important, so is the internal environment within each individual infected cell, where transcription factors such as XBP-1 binding viral promoters can alter the viral life cycle (69)(70)(71)(72). One of the most important functions of RTA is the ability to initiate a downstream cascade of viral gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…While the external cellular environment is important, so is the internal environment within each individual infected cell, where transcription factors such as XBP-1 binding viral promoters can alter the viral life cycle (69)(70)(71)(72). One of the most important functions of RTA is the ability to initiate a downstream cascade of viral gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In MHV-68 infection XBP-1 was found to transactivate Rta in vitro; however, it was dispensable for reactivation after in vivo infection. In contrast, IRF4 was found to be essential for reactivation in vivo following MHV-68 infection due to its requirement in the generation of plasma cells (73). In this study, we found a cell-intrinsic defect in plasma cell differentiation in the miR-155 KO mice, which led to a 2-fold difference in the proportion and absolute number of plasma cells compared to the levels in the WT controls.…”
Section: Discussionmentioning
confidence: 44%
“…The physiologic signals that control the switch from latency to lytic replication are unclear, but in cell culture viral reactivation has often been linked to exposure to stress-inducing stimuli. ER stress can trigger reactivation of EBV, KSHV and murine gammaherpesvirus 68 (MHV68) [119][120][121][122]. Lytic reactivation in response to ER stress is primarily due to XBP1s (Figure 2).…”
Section: Gammaherpesviruses and The Uprmentioning
confidence: 99%
“…Control of MHV68 latent/lytic switch by XBP1s is only partially conserved; XBP1s transactivates the MHV68 RTA gene in vitro, but in vivo the plasma cell differentiation factor interferon regulatory factor 4 (IRF4) serves in this role [120]. The ER-localized MHV68 M1 protein is induced by RTA and IRF4 and may also play a role in reactivation from latency [136,137].…”
Section: Gammaherpesviruses and The Uprmentioning
confidence: 99%